2018
DOI: 10.1111/eth.12770
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles in white‐rumped swallows (Tachycineta leucorrhoa) show a trade‐off between nest defense and chick feeding

Abstract: Studies about personalities in wild animals usually focus on five categories of behavioral traits that do not easily accommodate all aspects of parental care, a class of behaviors with direct consequence to reproductive success. Parental care can vary consistently between individuals and constitute parenting styles. Here we investigate the consistency of four behaviors of parental care across two breeding seasons of white‐rumped swallows Tachycineta leucorrhoa in southern Brazil. These behaviors are a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
1
7
1
Order By: Relevance
“…Unlike what has been described by others (Wischoff et al ), we found no evidence of a ‘breeding‐pair’ effect on individual measurements of exploratory behavior and aggressiveness, as revealed by both intra‐pair behavioral correlations and mixed‐effects models. This is important given that the majority of individuals included in our study were sampled as part of a social pair.…”
Section: Discussioncontrasting
confidence: 85%
“…Unlike what has been described by others (Wischoff et al ), we found no evidence of a ‘breeding‐pair’ effect on individual measurements of exploratory behavior and aggressiveness, as revealed by both intra‐pair behavioral correlations and mixed‐effects models. This is important given that the majority of individuals included in our study were sampled as part of a social pair.…”
Section: Discussioncontrasting
confidence: 85%
“…Defence behaviour of Chilean Swallow pairs breeding in North Patagonia consisted of dives, circling flights and increased vocal activity in association with In most aspects evaluated in this study, the antipredator responses observed for breeding Chilean Swallow adults were similar to those of Northern Hemisphere congeners (Shields 1984, Winkler 1991, 1992, 1994, which also display dives and circling flights around the predator. Moreover, dives and circling flights seem to be common in negative interactions because they were also used in aggressive conspecific interactions in the White-Rumped Swallow Tachycineta leucorrhoa (Wischhoff et al 2018). The rapid response of other Chilean Swallows (possibly, pairs and their neighbours), who gathered within seconds, is also in line with behaviours recorded for swallows in other genera (e.g.…”
Section: Discussionsupporting
confidence: 69%
“…Southern species have smaller clutches, lower nestling growth rates, and longer nestling periods than northern species (Massoni et al 2007, Liljesthrom 2011, Ospina et al 2015. While anti-predatory behaviours are largely known for northern congeners (Winkler 1991(Winkler , 1992, studies on the southern species are recent and scant (Wischhoff et al 2018).…”
mentioning
confidence: 99%
“…However, the specifics of the ecology of the species is likely to affect the importance females put on consistency. In systems where partners do not interact after mating, there may be less reason to expect differences between the sexes in terms of consistency [90,91]. enhance offspring fitness.…”
Section: Indirect Benefitsmentioning
confidence: 99%